Pengembangan Sistem Pengambilan Keputusan Yang Berkualitas Bagi UKM Melalui Penerapan Sistem Akuntansi Manajemen Berbasis Teknologi Informasi - Riskin Hidayat; Siti Alliyah (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2013)
This research aims to test the effect of the use of information technology to the quality of decisions through the characteristics of management accounting system (SAM) with interdependence as a moderating variable. This research use survey method with sampel is Small and Medium Enterprises (SMEs) in Kabupaten Rembang, with cluster sampling obtained sample 138 SMEs. Analysis of the data using linear regression. Result of research refer that information technology have an influence on positive to SAM and SAM have an influence on positive to quality of decisions. This suggest that SAM can indirectly mediate the relationship between information technology with decision quality. Morever, this research also refer that the SAM influence on the quality of decisions is stronger when moderated by interdependence.